På fältet — i "labbet": Video som inter-zonalt objekt - Andersdotter, Gunnel (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
In this article video recording and analysis in contemporary ethnological research is discussed. The dissertation work in question is within the field of culture and new technology. It pays special attention to people being shaped and shaping gender and profession in relation to objects in and around a workplace; a contemporary software technology company. The ethnologist herself has in her daily work stepped out of "pure" ethnology and situated herself in a multi academic setting within a technical university collage in Sweden. Video recording and analysis is emphasised as a possibility to open up the research process in different directions. Video is argued to act like, what Susan Leigh Star (1989) calls a boundary object. Such objects "both inhabit several intersecting social worlds and satisfy the informational requirements of each". Video is argued to facilitate co-constructive analytic activity in the research process. This activity involves both the software designers at the field site as well as colleagues from different academic disciplines. Co-operation is facilitated, but without forcing consensus.